THE USE OF AFFIXATION ON STUDENTS’ WRITING TEXT AT THE SECOND GRADE OF SMAN 1 KOTA JAMBI - Rozelin, Diana; Indriyani, Tuti; Suryani, Hilma; Nurhasianti (JR-ELT (Journal of Research in English Language Teaching), 2020)
The aims of this study investigates about two type of affixation focused on derivational affixes use by students of SMAN1 Jambi City in writng text.the data of the study are on students writing text. The method of the research was qualitative research and the approach used in counducting this research was descriotive research. The data obtained through documentation. This study involved twenty five students of XI mipa at SMAN1 Jambi City as sample the result of the research showed that there two type of affixation use by the students on their writing text, it shows there are, verb maker (38), noun maker (123), adjective maker ( 56), and adverb maker (127), the totals affixes use 344 word affixes.The researcher uses the classification of affixes by using Fromkin, et al (2014)’s theory about derivation which change grammatical classes which included noun , verb, adjective, and adverb.The findings of the study reveal that from 344 words which consist of affixes that focuse derivational affixes. that grammatical classes which involve 123 for noun which affixes produced are – ation, -ion, -er, -dis,- extra-ence, -er,, -ment,, -ness. 56 for adjective which affixes produced are –ous, - able, -ful, -y, -in, -ir, -ate, -tic, -ive,-al, -less, 127 for adverb which affix produced are –ly, -less, -un, -a, -im, -eag, and 38 for verb which affixes produced are -be-, and -ize. The intended meanings are about the affixation focuse of derivational affixation words that related to the quotations that are analyzed.